The effects of bisphosphonates on ectopic soft tissue mineralization caused by mutations in the ABCC6 gene - Li, Qiaoli (Cell Cycle, 2015)
Pseudoxanthoma elasticum (PXE) and generalized arterial calcification of infancy (GACI) are heritable ectopic mineralization disorders. Most cases of PXE and many cases of GACI harbor mutations in the ABCC6 gene. There is no effective treatment for these disorders. We explored the potential efficacy of bisphosphonates to prevent ectopic calcification caused by ABCC6 mutations by feeding Abcc6(−/−) mice with diet containing etidronate disodium (ETD) or alendronate sodium trihydrate (AST) in quantities corresponding to 1x, 5x, or 12x of the doses used to treat osteoporosis in humans. The mice were placed on diet at 4 weeks of age, and the degree of mineralization was assessed at 12 weeks by quantitation of the calcium deposits in the dermal sheath of vibrissae, a progressive biomarker of the mineralization, by computerized morphometry of histopathologic sections and by direct chemical assay of calcium. We found that ETD, but not AST, at the 12x dosage, significantly reduced mineralization, suggesting that selected bisphosphonates may be helpful for prevention of mineral deposits in PXE and GACI caused by mutations in the ABCC6 gene, when combined with careful monitoring of efficacy and potential side-effects.